Finding Similar Failures using Callstack Similarity - Bartz, Kevin; Stokes, Jay; Platt, John; Kivett, Ryan; Grant, David; Calinoiu, Silviu; Loihile, Gretchen (SysML08: Third Workshop on Tackling Computer Systems Problems with Machine Learning Techniques, 2008)
We develop a machine-learned similarity metric for Windows failure reports using telemetry data gathered from clients describing the failures. The key feature is a tuned callstack edit distance with learned costs for seven fundamental edits based on callstack frames. We present results of a failure similarity classifier based on this and other features. We also describe how the model can be deployed to conduct a global search for similar failures across a failure database.